Comment on: "Hyperfine structure measurements of Co I and Co II with Fourier transform spectroscopy" by Fu et al. [JQSRT 2021, 107590]. (September 2022) - Ding, Milan; Pickering, Juliet C.
Highlights: Fu et al. (2021) published a hyperfine structure analysis of 61 Co II energy levels without reference to the existing extensive study in the literature of Ding and Pickering (2020). 43 Co II magnetic hyperfine interaction constants published by Fu et al. were in agreement within uncertainties with those published previously by Ding and Pickering. Large discrepancies were found in 17 Co II magnetic hyperfine interaction constants of Fu et al. The new A constant of 3d 6 4s 2 a 5 D 4 reported by Fu et al. is found to agree with observations by Ding & Pickering. Fu et al. had analysed experimentally unclassified lines at Ritz wavenumbers 25453.968 cm − 1 and 25149.948 cm − 1 to attempt to determine the magnetic hyperfine structure constants of energy levels 3d 7 ( 2 G)4s a 3 G 5 and 3d 7 ( 2 P)4s c 3 P 2 respectively. This caused most of the discrepancies. Abstract: This comment points out errors in the analysis of 61 magnetic hyperfine structure ( A ) constants of Co II energy levels by Fu et al. [JQSRT 2021, 107590]. The paper was published without full awareness of the extensive literature already available for Co II hyperfine A constants at the time; 57 of 58 A constants that were claimed to have been measured for the first time had already been measured by the prior work of Ding and Pickering [ApJS 2020, 251:24], who had published A constants for 292 levels of Co II. The A constant of 3d 6 4s 2 a 5 D 4 has been determined by Fu et al. [JQSRT 2021, 107590] for the first time to be 12.0 ± 1.8 mK (1 mK = 0.001 cm − 1 ), which was found to agree with line profiles observed by Ding and Pickering [ApJS 2020, 251:24]. Discrepancies in 17 A constants of Fu et al. [JQSRT 2021, 107590] were found, which are likely due to the analysis of weak, experimentally unclassified transitions with Ritz wavenumbers 25453.966 cm − 1 and 25149.948 cm − 1 by Fu et al. [JQSRT 2021, 107590] for the A constants of the energy levels 3d 7 ( 2 G)4s a 3 G 5 and 3d 7 ( 2 P)4s c 3 P 2 respectively. Fewer transitions and poorer quality spectra analysed by Fu et al. [JQSRT 2021, 107590] are also concluded to have contributed to disagreements in the 17 A constants.